Magnetic properties of rotational bands in 160Dy and 170–174Yb isotopes - Okhunov, Abdurahim; Al-Sammarrae, Anwer Ahmed; Abu Kassim, Hasan (Institute of Physics Publishing (UK), 2013)
In this work, non - adiabatic effects manifested in the magnetic properties of lowlying states of even-even deformed nuclei are studied. A simple phenomenological model which takes into account the Coriolis mixing of states of the ground and K = 2+nand K = 1+ bands are proposed. The Calculations for isotopes 160Dy and 170;172;174Y b, are carried out. The calculated gR– factor for the states of ground band which are compared with experimental data. Decreases of gR– factor with increasing angular momentum I have been discussed. The probability of M1– transition from 1+ and coefficients of multipole mixture (E2=M1) from 0+ 2 , 0+ 3 , 2+ 1 , and 2+ 2 bands are calculated and compared with the experimental data. Decreases of gR– factor with increasing angular momentum I have been discussed. That these is an obvious inverse relation between gR– factor and angular momentum I of the ground band states. This has been explained by a mixing ground and K = 1+ bands which have a strong B(M1) to ground state.